Implementation of lean manufacturing in multinational companies with production subsidiaries in Brazil : a roadmap - Göhner, Lara (2017)
Multinational companies with production subsidiaries in Brazil are generally recognized as being highly productive companies. However, in large, their productivity potential is not fully achieved. Lean Manufacturing (LM) has proved to be a valuable aid to achieve competitiveness in the long run. In the light of the increasing importance of the successfully implementation of LM by multinationals in Brazil and an apparent lack of discussion regarding LM in Brazil, this paper aims to propose a comprehensive implementation roadmap, to enable multinationals to achieve an advanced sustainable LM system in a practical manner, based on a systematic approach. Findings from the literature and case studies are combined to develop the roadmap, to permit both companies that have, and have just started to implement LM to be able to use the roadmap. The roadmap was built on a broad empirical basis and it is impossible to consider all factors influencing LMI in multinationals operating in Brazil in a real world setting. Accordingly, it should not be regarded as a ready-made implementation plan, which has to be strictly followed, but rather a guideline to help multinationals develop their own, detailed and tailor-made plan to successfully implement LM and to establish a learning organization.